Faktor-Faktor yang Mempengaruhi Ketidakpatuhan Berobat pada Penderita Tuberkulosis Paru - Erni Erawatyningsih, Purwanta, Heru Subekti (Berita Kedokteran Masyarakat (BKM), 2009)
Background: Tuberculosis (TB) disease is one of major public health problems which cannot be overcome yet. The problem is caused by some factors one of which is incompliance of the patient with medication. In 2005, At the health center of  West Dompu drop out rate of TB patients was still relatively high  (29.1%) and  recovery patients TB  were still relatively low (71,7%).Objective: To identify factors which affect incompliance with medication among lung TB patients at the working area of West Dompu health center, Subdistrict of Woja, District of Dompu, West Nusa Tenggara.Method: This was an analytical case study with case control design. Samples of the study were 21 patients of lung TB totally taken who failed and were dropped out from medication in 2005. Instrument this study used quesionary. Data analysis used chi square.Result: The factor most dominantly affected incompliance with medication among lung TB patients was education (OR=0.12, p<0.05); whereas factors which did not affect incompliance with medication were age, sex, quality of service, support from drug taking supervisor and distance from the house to the health center (p>0.05).Conclusion: Education, knowledge, family income, and duration of illness and drug side effects significantly affected incompliance with medication among lung TB patients and education was the most dominant factor.Keywords: lung tuberculosis, incompliance